PERANCANGAN FONDASI TERMINAL INTERNATIONAL CONTAINER CARGO PELABUHAN GRESIK - Jeson Tjowari, Alexander
Gresik Port’s international cargo terminal is a facility mainly designed for loading and unloading activities of international cargo. This final project focuses on the foundation design for the cargo terminal. The first step of foundation design starts from interpretating soil data based on field and laboratory test. Based on the soil data, the soil design parameters are determined to be used in designing the foundation dimensions. Based on the location of the cargo terminal which is located at the middle of the sea, the type of foundation used on the terminal foundation design is steel pipe driven pile foundation where the pile foundation is modeled as deck on pile. While modeling the pile foundation, it is necessary to locate the fixity point and the value of the lateral spring stiffness which will be modeled as soil interaction in the pile modeling. Based on the modeling results, the load that will be received by the foundation will be analyzed for the pile foundation, namely axial bearing capacity, lateral bearing capacity, and the settlement of the pile foundation. In the axial bearing capacity analysis, an analysis of the compressive and tensile bearing capacity will be carried out where the carrying capacity will be compared with the load to be received by the pile foundation based on the design criteria. In the analysis of lateral bearing capacity, the p-y method will be used, where based on the design criteria the allowable deflection will be used to calculate the lateral capacity of the pile foundation and the compared with the lateral load that will be received by the pile. In settlement analysis, the elastic settlement and consolidation settlement will be compared based on the allowable settlement and allowable differential settlement. The design of the foundation is obtained after doing design iterations where the bearing capacity and settlement of the foundation meet all the design criteria.